Singapore's Japanese community : a study in migration, acculturation, and transforming identities (1920-1942, 1970-1995) - Yuri Yamaguchi (Nanyang Technological University, 2020)
Most studies on the Japanese in Singapore focus on the occupation period and Japan’s economic push into Singapore during the post-war period. Absent from these discussions, however, is the focus on the migratory experiences of the Japanese coming to Singapore during the pre-war (1920-1942) and post-war (1970-1995) periods. Neither has there been research comparing the socio-economic differences between the pre-war and post-war generations of Japanese in Singapore. Where Japan had once been an expanding imperialist power, it became an economic powerhouse after the war. Singapore transformed from a British colony to a trading and financial centre. This paper aims to question how such transformations impacted the experiences of the pre-war and post-war Japanese in acculturating into Singapore’s society, with interest in how changes in concepts of their identity influenced these experiences. It argues that the pre-war Japanese acculturated to Singapore to a larger extent than the post-war Japanese. Before the war, the motivations behind Japanese expansion into Southeast Asia, the favourable political and economic climate in Singapore, and the Japanese identity being predicated on assimilation facilitated a greater degree of Japanese acculturation. Conversely, the post-war Japanese were largely short-term expatriates and their families who tended to keep within the Japanese community. This is due to Japan’s economic expansion into Southeast Asia, the stringent immigration policies in Singapore which favoured professionals, and the development of a Japanese national identity that stressed homogeneity and conformation.